Low Level Laser Therapy - Jain, Anukriti; Akbar Ali, Syed; Shrivastava, Trilok; Shukla, Chandresh; Dixit, Siddharth; Patel, Aakash (Journal of Neonatal Surgery, 2025)
Low level laser therapy (LLLT) is a non-invasive accessory in contemporary orthodontics. Derived out of the idea of biostimulation, LLLT also uses photobiomodulation as its principle by which cells may be stimulated to repair tissues, i.e. by increasing the production of ATP in mitochondria and the expression of various genes. The therapy has demonstrated encouraging clinical benefits like faster orthodontic tooth movement (OTM) via improvement of alveolar bone remodeling by activation of osteoclast and osteoblast. Moreover, LLLT is a safe, non-invasive, and nonsteroidal alternative to the nonsteroidal anti-inflammatory drugs (NSAIDs) in the treatment of treatment-related pain through enhancement of microcirculation and decreasing inflammatory mediators. Other advantages discussed in the review are that it may prevent orthodontically induced inflammatory root resorption (OIIRR), faster healing of soft tissue and periodontal wounds, also the pain treatment of temporomandibular disorders (TMD). Although these power benefits exist, the review points out that absence of standardized clinical protocols which is a product of extensive disparities in the parameters and application techniques of laser is currently a setback to routine practice. Therefore, more clinical trials are necessary to develop the best and standardized guidelines that will make LLLT an indispensable part of patient centered care in orthodontics